Studi ilmu falak : cara mudah belajar ilmu falak / H. Ahmad Izzan, Iman Saifullah ; editor Dendi Riswandi, Rizki Kusuma Wardhani. - AHMAD IZZAN, H, 1964-; Iman Saifullah; Dendi Riswandi (Pustaka Shuhuf Media (Pam Press), 2013)
182 hlm. : ilus. ; 21 cm